Who can you trust? Behavioral and neural differences between perceptual and memory-based influences - Rudoy, John D.; Paller, Ken A. (Frontiers in Human Neuroscience, 2009)
Decisions about whether to trust someone can be influenced by competing sources of information, such as analysis of facial features versus remembering specific information about the person. We hypothesized that such sources can differentially influence trustworthiness judgments depending on the circumstances in which judgments are made. In our experiments, subjects first learned face-word associations. Stimuli were trustworthy and untrustworthy faces selected on the basis of consensus judgments and personality attributes that carried either the same valence (consistent with face) or the opposite valence (inconsistent with face). Subsequently, subjects rated the trustworthiness of each face. Both learned and perceptual information influenced ratings, but learned information was less influential under speeded than under non-speeded conditions. EEG data further revealed neural evidence of the processing of these two competing sources. Perceptual influences were apparent earlier than memory influences, substantiating the conclusion that time pressure can selectively disrupt memory retrieval relevant to trustworthiness attributions.